2009
DOI: 10.1007/s12526-009-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and diversity of polychaetes (Annelida) in the deep Weddell Sea (Southern Ocean) and adjacent basins

Abstract: During the austral summer of 2005, the Weddell deep sea and adjacent basins were sampled in the course of the ANDEEP III project. In this study, 19 epibenthic-sledge stations are analyzed, with a focus on species diversity and distribution patterns of polychaetes. The polychaete fauna of the deep Southern Ocean has been found to be similarly speciose and diverse compared with deep-sea basins worldwide. Also, in depths below 2,000 m many polychaete species do not seem to be endemic for certain areas but are rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Gray et al (1997) also concluded that evenness in the deep sea is higher than in shallower coastal environments. Extensive polychaete data sets from the recent ANDEEP expeditions to the Weddell Sea shelf and slope and Southern Ocean abyssal plain are also consistent with observations of high evenness at abyssal sites relative to Antarctic shelf sites (Schüller & Ebbe 2007, Schüller et al 2009). Antarctic shelf and slope polychaetes thus appear to approach other temperate and tropical bathyal/abyssal environments in diversity, but in general species richness is slightly lower and dominance is much higher.…”
Section: Antarctic Benthic Diversity In a Regional And Global Contextsupporting
confidence: 72%
See 1 more Smart Citation
“…Gray et al (1997) also concluded that evenness in the deep sea is higher than in shallower coastal environments. Extensive polychaete data sets from the recent ANDEEP expeditions to the Weddell Sea shelf and slope and Southern Ocean abyssal plain are also consistent with observations of high evenness at abyssal sites relative to Antarctic shelf sites (Schüller & Ebbe 2007, Schüller et al 2009). Antarctic shelf and slope polychaetes thus appear to approach other temperate and tropical bathyal/abyssal environments in diversity, but in general species richness is slightly lower and dominance is much higher.…”
Section: Antarctic Benthic Diversity In a Regional And Global Contextsupporting
confidence: 72%
“…For example, at the DOMES site in the abyssal Pacific, the sampling area was approximately 100 times as large as the sample area for the 3 FOODBANCS stations, but the number of specimens was approximately the same and the number of species recorded at the FOODBANCS sites was approximately 25% lower (Table 4). Schüller et al (2009) also reported comparable levels of polychaete diversity at Antarctic sites sampled during the ANDEEP III expedition relative to abyssal Altantic meso trophic and oligotrophic sites (Cosson-Sarradin et al 1998), although sampling methods again differed be tween studies. Rarefaction estimates from these studies also correspond well with our data and those from the EASIZ study (Hilbig 2001), but are lower than those reported for other temperate and tropical abyssal sites.…”
Section: Antarctic Benthic Diversity In a Regional And Global Contextmentioning
confidence: 85%
“…Schüller & Ebbe, ) and thus cannot be considered as valid according to the ICZN. Moreover, the description in Schüller () suggests strongly that this material belongs to a different genus (probably Micropodarke ). Finally, note that the generic name Oxydromus Grube, has been recently reinstated over Ophiodromus Sars, (Villalobos‐Guerrero & Harris, ).…”
Section: Discussionmentioning
confidence: 91%
“…However, Pleijel () finally retained P. blacki , as well as the other two species previously allocated by Pettibone (), within Parasyllidea . A fourth species, Parasyllidea delicata , was described as a part of a PhD thesis (Schüller, ). However, the species description was not included in the formally published version of the PhD (Schüller, ) or in the associated published paper (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the isopods and polychaetes, slope assemblages included species that have invaded from either the shelf or the abyss through emergence or submergence, respectively, whereas in other taxa such as bivalves and gastropods, the shelf and slope assemblages were more distinct. Abyssal faunas tended to have stronger biogeographic links to other oceans, particularly the Atlantic, but mainly for organisms with good dispersal capabilities such as the foraminiferans (Brandt et al 2007b ;Pawlowski et al 2007 ) and polychaetes (Sch ü ller & Ebbe 2007 ;Sch ü ller et al 2009 ). The isopods, ostracods, and nematodes, which are poor dispersers, include many species currently known only from the Southern Ocean.…”
Section: Diversity and B Iogeography Of Antarctic D Eep -S Ea F Aunamentioning
confidence: 99%